Receptor Interacting Protein Kinases 1/3: The Potential Therapeutic Target for Cardiovascular Inflammatory Diseases - Leng, Yiming; Zhang, Ying; Li, Xinyu; Wang, Zeyu; Zhuang, Quan; Lu, Yao (Frontiers in Pharmacology, 2021)
The receptor interacting protein kinases 1/3 (RIPK1/3) have emerged as the key mediators in cell death pathways and inflammatory signaling, whose ubiquitination, phosphorylation and inhibition could regulate the necroptosis and apoptosis effectually. Recently, more and more studies show great interest in the mechanisms and the regulator of RIPK1/3-mediated inflammatory response and in the physiopathogenesis of cardiovascular diseases. The crosstalk of autophagy and necroptosis in cardiomyocyte death is a nonnegligible conversation of cell death. We elaborated on RIPK1/3-mediated necroptosis, pathways involved, the latest regulatory molecules and therapeutic targets in terms of ischemia reperfusion, myocardial remodeling, myocarditis, atherosclerosis, abdominal aortic aneurysm, and cardiovascular transplantation, etc.